Magnetohydrodynamic flow around an elongated cylinder in non-Darcian porous regime with higher order chemical reaction and Soret/Dufour effects - Das, Utpal Jyoti; Begum, Jubi (Zielona Góra: Uniwersytet Zielonogórski)
Here, we consider magnetohydrodynamic flow of an incompressible, time independent fluid past an elongated cylinder surrounded in a non-Darcian porous regime with magnetic flux supplied at an acute angle. The Soret/Dufour effects and the higher order chemical reactions are also included in the present study. The subsequent governing equations are resolved using the MATLAB-bvp4c method.
Keywords: inertia parameter; magnetohydrodynamics; Soret number; Dufour number; porous medium; elongating cylinder; bvp4c